Investigating palygorskite's role in the development of mesothelioma in southern Nevada: Insights into fiber-induced carcinogenicity. (17th August 2016) - Larson, David; Powers, Amy; Ambrosi, Jean-Paul; Tanji, Mika; Napolitano, Andrea; Flores, Erin G.; Baumann, Francine; Pellegrini, Laura; Jennings, Cormac J.; Buck, Brenda J.; McLaurin, Brett T.; Merkler, Doug; et al.
ABSTRACT: Similar to asbestos fibers, nonregulated mineral fibers can cause malignant mesothelioma (MM). Recently, increased proportions of women and young individuals with MM were identified in southern Nevada, suggesting that environmental exposure to carcinogenic fibers was causing the development of MM. Palygorskite, a fibrous silicate mineral with a history of possible carcinogenicity, is abundant in southern Nevada. In this study, our aim was to determine whether palygorskite was contributing to the development of MM in southern Nevada. While palygorskite, in vitro, displayed some cytotoxicity toward primary human mesothelial (HM) cells and reduced their viability, the effects were roughly half of those observed when using similar amounts of crocidolite asbestos. No Balb/ c (0/19) or MexTAg (0/18) mice injected with palygorskite developed MM, while 3/16 Balb/ c and 13/14 MexTAg mice injected with crocidolite did. Lack of MM development was associated with a decreased acute inflammatory response, as injection of palygorskite resulted in lower percentages of macrophages ( p = .006) and neutrophils ( p = .02) in the peritoneal cavity 3 d after exposure compared to injection of crocidolite. Additionally, compared to mice injected with crocidolite, palygorskite-injected mice had lower percentages of M2 (tumor-promoting) macrophages ( p = .008) in their peritoneal cavities when exposed to fiber for several weeks. Our study indicates that palygorskite found in the environment in southern Nevada does not cause MM in mice, seemingly because palygorskite, in vivo, fails to elicit inflammation that is associated with MM development. Therefore, palygorskite is not a likely contributor to the MM cases observed in southern Nevada.